The Pandora’s box of transparency opened by direct-to-consumer genetic testing - Saruwatari Zavala, Garbiñe (Frontiers in Genetics, 2023)
With the increasing use of direct-to-consumer (DTC) genetic testing, several cases of fertility fraud have been uncovered throughout the world. A review of newspaper articles and specialized literature was made to analyze the issue of fertility fraud. The most famous cases, some of which are narrated in this article, became a scandal because they were committed by the doctors who treated the patients in question as a routine procedure in their medical practice. Some have been widely exposed in documentaries on streaming platforms, thereby raising awareness about a grave problem. The discussion focuses on the ambiguous regulation on the anonymity of donors, which has been one of the elements of the deception committed against the families using these services. Anonymity nowadays collides with the fascinating Pandora’s box of transparency in genetic information that has been opened by DTC genetic testing.